Adaptation of seed dormancy to maternal climate occurs via intergenerational transport of abscisic acid - Xiaochao Chen; William Bezodis; Pablo González-Suárez; Vanda Knitlhoffer; Andrew Goldson; Ashleigh Lister; Iain Macaulay; Steven Penfield (Proceedings of the National Academy of Sciences, 2025)
How or whether organisms can inherit parental adaptations to the prevailing environment is a major topic in biology. In plants, seed traits such as size, yield, and dormancy are all affected by the environment during reproduction, but whether developing progeny sense temperature within the fruit or whether seasonal climate information is inherited intergenerationally from the parents remains unclear. In this study, we use intergenerational single-nucleus omics to understand the mechanisms underlying the effects of seasonal temperature changes in fruits containing developing seeds of the next generation. We show that the sensing of temperature takes place specifically in maternal fruit tissues and that mothers preadapt their progeny to maternal temperature through the intergenerational flux of the hormone ABA to the zygote itself where it is sensed to affect dormancy. We conclude that mothers can control filial traits via direct transfer of hormones to progeny and propose that this is an important mechanism by which populations can rapidly adapt to environmental change.